The Role of Children's Age and Gender, and Friends' Gender in the Children's Interaction towards Social Problem Solving Strategies in Preschool Children - Izzaty, Rita Eka (Psychological Research and Intervention, 2020)
Social problem-solving strategy accepted by society is the essential accomplishments in the development of pre-school children. However, until recent studies, social problem-solving strategies among pre-school children in Indonesia is still rarely conducted. This research examines the role of age, gender in children, and friends' gender towards social problem-solving strategies. This research utilised a purposive sampling that voluntarily involved 162 children    4-6 years old. Those children were selected from an intact family consisting of a father, mother and children who lived together.    A hypothetical social situation dilemma was utilised to gather social problem-solving strategies data from the subjects.  The data were analysed with the use of cross-tabulation and chi-square test. Concerning the data analysis, the results reveal no significant difference in social problem-solving strategies when viewed in terms of age and gender of the children and friends' gender. This suggests that children ages 4 to 6 years for boys and girls still have the same patterns of social behaviour dealing with similar gender and different ones.